Lateral root emergence in Arabidopsisis dependent on transcription factor LBD29 regulation of auxin influx carrier LAX3 - Porco, Silvana; Larrieu, Antoine; Du, Yujuan; Gaudinier, Allison; Goh, Tatsuaki; Swarup, Kamal; Swarup, Ranjan; Kuempers, Britta; Bishopp, Anthony; Lavenus, Julien; Casimiro, Ilda; Hill, Kristine; et al. (Company of Biologists, 2016)
Lateral root primordia (LRP) originate from pericycle stem cells located deep within parental root tissues. LRP emerge through overlying root tissues by inducing auxin-dependent cell separation and hydraulic changes in adjacent cells. The auxin-inducible auxin influx carrier LAX3 plays a key role concentrating this signal in cells overlying LRP. Delimiting LAX3 expression to two adjacent cell files overlying new LRP is crucial to ensure that auxin-regulated cell separation occurs solely along their shared walls. Multiscale modeling has predicted that this highly focused pattern of expression requires auxin to sequentially induce auxin efflux and influx carriers PIN3 and LAX3, respectively. Consistent with model predictions, we report that auxin-inducible LAX3 expression is regulated indirectly by AUXIN RESPONSE FACTOR 7 (ARF7). Yeast one-hybrid screens revealed that the LAX3 promoter is bound by the transcription factor LBD29, which is a direct target for regulation by ARF7. Disrupting auxin-inducible LBD29 expression or expressing an LBD29-SRDX transcriptional repressor phenocopied the lax3 mutant, resulting in delayed lateral root emergence. We conclude that sequential LBD29 and LAX3 induction by auxin is required to coordinate cell separation and organ emergence.